Victims of intimate partner violence more likely to report abuse from in-laws. - Raj, Anita; Livramento, Kaí N; Santana, M Christina; Gupta, Jhumka; Silverman, Jay G (Violence against women, 2006)
The current study of South Asians in the United States was designed to assess quantitatively the association between intimate partner violence (IPV) and emotional abuse by in-laws (n=169) and to qualitatively identify via in-depth interviews with battered women (n=23) forms of abuse perpetrated by in-laws. Quantitative findings demonstrate a significant relationship between IPV and abuse from in-laws (odds ratio=5.7, 95% confidence interval=1.5-21.5). Qualitative data demonstrate that abuse by in-laws includes emotional abuse (e.g., isolation, social and economic control, and domestic servitude), awareness or support of IPV, and direct physical abuse. Domestic violence interventions with South Asian women must consider abuse from in-laws and IPV experiences.
Keywords: Adult; Aged; Asian Americans; Battered Women; Cross-Sectional Studies; Disclosure; Female; Humans; Intergenerational Relations; Middle Aged; Narration; Questionnaires; Risk Factors; Socioeconomic Factors; Spouse Abuse; United States; Women's Health